Electrochemical impregnation of silver nanostructures in titanium dioxide nanotubes - Ng, Siow Woon; Yam, F. K.; Hassan, Zainuriah (Journal of The Electrochemical Society, 2012)
Highly-ordered titanium dioxide nanotubes arraywas prepared in fluoride based electrolyte andwas subsequently deposited with silver nanoparticles and decorated by silver dendritic structures in silver ions-rich ethanolic electrolyte through conventional two-electrode configuration electrochemical method. The nanoparticles conglomerated at the surface of titanium dioxide nanotubes to form a hierarchy dendritic nanostucture, analogous to a structure consists of a trunk with branches and leaves, through the diffusion-limited aggregation mechanism and oscillatory character in nucleation kinetics. Structural investigation by X-ray diffraction measurements revealed that titanium dioxide nanotubes are comprised of multiple anatase and rutile phases. The finding is aligned with the observation of active anatase and rutile Raman modes through Raman measurements. In comparison of silver loaded titanium dioxide nanotubes to unloaded nanotubes in Raman measurements, surface-enhanced Raman scattering effect was demonstrated by silver incorporated samples whereby the Raman signal is intensified to more than sixfold in certain sample. © 2012 The Electrochemical Society.
CRIS-Team Scopus Importer:2022-11-02